2002
DOI: 10.1055/s-2002-36849
|View full text |Cite
|
Sign up to set email alerts
|

PHACE Syndrome: New Views on Diagnostic Criteria

Abstract: The association of large facial hemangiomas with posterior fossa malformations and vascular anomalies has been termed the PHACE syndrome. It is characterized by the association of posterior fossa malformations, hemangiomas, arterial anomalies, coarctation of the aorta and other cardiac defects, and eye abnormalities. Since most articles focus on isolated case reports, an extended retrospective literature review of all reports of large hemangiomas with associated abnormalities of the central nervous system and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…There have been reports of several cases of intracranial lesions demonstrating imaging characteristics and treatment responses similar to extracranial capillary hemangiomas [12,13,14,15]. It is possible that there have been asymptomatic cases harboring intracranial capillary hemangiomas that regressed unrecognized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been reports of several cases of intracranial lesions demonstrating imaging characteristics and treatment responses similar to extracranial capillary hemangiomas [12,13,14,15]. It is possible that there have been asymptomatic cases harboring intracranial capillary hemangiomas that regressed unrecognized.…”
Section: Discussionmentioning
confidence: 99%
“…A review by Poetke et al [13 ]stated that 12% of patients with PHACE syndrome had intracranial hemangiomas. Following the first report of PHACE syndrome by Frieden et al [25 ]in 1996, more than 200 cases have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The overall frequency of posterior fossa anomalies in patients with PHACE varies by published report from 30.4% to 81%. 7,14,16 In a study characterizing the neuroimaging features of PHACE, 24 (41%) of 59 patients had structural brain abnormalities detected. 17 All brain lesions that were unilateral had associated cerebral arteriopathy and cutaneous hemangioma on the ipsilateral side.…”
Section: Methodsmentioning
confidence: 99%
“…Between 43% and 90% of patients with PHACE have a central nervous system (CNS) structural malformation2,5,6,9,15). Our patient also exhibited a posterior fossa anomaly, Dandy-Walker variant.…”
Section: Discussionmentioning
confidence: 99%